In vitro antiproliferative activity of partially purified Trigona laeviceps propolis from Thailand on human cancer cell lines - Puthong Songchan; Phuwapraisirisan Preecha; Umthong Supawadee; Chanchao Chanpen (BMC, 2011)
Abstract Background Cancers are some of the leading causes of human deaths worldwide and their relative importance continues to increase. Since an increasing proportion of cancer patients are acquiring resistance to traditional chemotherapeutic agents, it is necessary to search for new compounds that provide suitable specific antiproliferative affects that can be developed as anticancer agents. Propolis from the stingless bee, Trigona laeviceps, is one potential interesting source that is widely available and cultivatable (as bee hives) in Thailand. Methods Propolis (90 g) was initially extracted by 95% (v/v) ethanol and then solvent partitioned by sequential extractions of the crude ethanolic extract with 40% (v/v) MeOH, CH2Cl2 and hexane. After solvent removal by evaporation, each extract was solvated in DMSO and assayed for antiproliferative activity against five cancer (Chago, KATO-III, SW620, BT474 and Hep-G2) and two normal (HS27 fibroblast and CH-liver) cell lines using the MTT assay. The cell viability (%) and IC50 values were calculated. Results The hexane extract provided the highest in vitro antiproliferative activity against the five tested cancer cell lines and the lowest cytotoxicity against the two normal cell lines. Further fractionation of the hexane fraction by quick column chromatography using eight solvents of increasing polarity for elution revealed the two fractions eluted with 30% and 100% (v/v) CH2Cl2 in hexane (30DCM and 100DCM, respectively) had a higher anti-proliferative activity. Further fractionation by size exclusion chromatography lead to four fractions for each of 30DCM and 100DCM, with the highest antiproliferative activity on cancer but not normal cell lines being observed in fraction# 3 of 30DCM (IC50 value of 4.09 - 14.7 μg/ml). Conclusions T. laeviceps propolis was found to contain compound(s) with antiproliferative activity in vitro on cancer but not normal cell lines in tissue culture. The more enriched propolis fractions typically revealed a higher antiproliferative activity (lower IC50 value). Overall, propolis from Thailand may have the potential to serve as a template for future anticancer-drug development.